Improving Students’ Pronunciation Skill Using Cake Application - I Kadek Berli Arya Sujana; Made Hery Santosa; Ni Wayan Surya Mahayanti (Journal of English Language Learning, 2024)
English language competency is crucial for success in the classroom and in the workplace in today's worldwide society. This study examines how sixth-grade students at SD N 1 Baktiseraga can improve their English pronunciation skills by using the CAKE application, a mobile-assisted language learning tool. Utilizing Classroom Action Research (CAR) over two cycles, this research involved 25 students and aimed to improve pronunciation through interactive and interesting technological methods. Initial observations indicated low levels of engagement and pronunciation challenges among students. This intervention involves a learning plan that incorporates the CAKE application, with a focus on everyday conversations and practical speaking exercises. Data collection includes pre-test and post-test to measure progress as well as observation data to assess student participation and engagement. The results showed significant improvements in students' pronunciation skills and increased class participation. Uniformity of pronunciation abilities among students also increased, indicating reduced variation in skills. This research shows the effectiveness of integrating mobile technology into language education, highlighting the role of the CAKE app in improving student pronunciation and engagement. These findings suggest that such technological tools can significantly improve language learning outcomes and should be considered for wider educational use.